PENGARUH PENGGUNAAN LKPD BERBASIS MODEL PROJECT BASED LEARNING (PjBL) PEMBELAJARAN IPAS TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Hartika, Della; Monanisa; Sugiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using a Project‑Based Learning (PjBL) model supported by Student Worksheets (LKPD) on the topic “Now I’ve Become More Orderly” (“Kini Aku Menjadi Lebih Tertib”) on elementary students’ learning outcomes. The research employed a pre‑experimental design with a quantitative approach, specifically a one‑group pre‑test–post‑test design. The participants were a single class of 33 elementary students. Instruments consisted of a learning‑achievement test and a student‑activity observation sheet. Data were analyzed using descriptive statistics and a t‑test to identify differences in learning outcomes before and after the implementation of the LKPD‑based PjBL model. The results show an improvement in students’ learning outcomes after the PjBL model was applied, demonstrating that the LKPD‑based PjBL instructional model is effective in enhancing students’ understanding of the importance of orderly living in daily life.